Association of a single-nucleotide polymorphism in C12orf43 region with the risk of coronary artery disease: Association of a SNP C12orf43 region with the risk of CAD - Qammar, Najma; Zain, Maryam; Jabeen, Raheela; Deeba, Farah; Iqbal, Nadia; Rashad Javeed, Hafiz Muhammad; Alatawi, Fatema Suliman; Alatawi, Mohsen Suliman; Almowallad, Sanaa; Alharbi, Amnah A.; Şahin, Hüseyin (Cellular and Molecular Biology, 2024)
The genetics of organisms play a vital role in the development of coronary artery disease (CAD), with its heritability estimated at approximately 50-60%. For this purpose, we examined the relationship between CAD risk and C12orf43/rs2258287 polymorphisms in the Pakistani population. In this study based on the genetic approach to dyslipidemia, a total of 200 subjects were included from the southern Punjab. The biochemical analysis of parameters (total cholesterol, triglycerides, blood glucose, high-density lipoprotein, and low-density lipoprotein) was carried out along with molecular analysis using an ARMS-PCR-based assay for single-nucleotide polymorphism (SNP) C12orf43/rs2258287 to identify the genotype. Genotypes showed a substantial correlation with both family history and metabolic markers. The cholesterol, low-density lipoprotein cholesterol (LDL-C), triglycerides and blood glucose levels were higher while the high-density lipoprotein cholesterol (HDL-C) level was lower significantly (p<0.05) in cases than in controls. Age, pulse rate, diabetes, physical activity, smoking, family history, and dietary habits were also significantly associated (p<0.05) with CAD individuals. The SNP C12orf43/rs2258287 also showed an association with CAD in the population of southern Punjab. Based upon this study, it could be concluded that CAD is characterized by an unfavorable lipid profile in association with SNP C12orf43/rs2258287.